: BPS - Ikhsan Margo Pangestu (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2019)
Along with the improvement in the percentage rate of poverty and the unemployment rate at the national level, there is still big homework to be completed regarding the disparity at the regional level. On the one hand, the distribution of unemployment rates by province tends to be equally distributed, while the poverty rate shows the opposite, in which there are still many provinces that have high poverty rates. Those conditions suggests an indication of the working poor problems in Indonesia. This study aims to analyze the phenomenon of working poor and analysis the influence of village fund policy, investment, and employment factors on working poor in 2015-2018. The method of analysis was carried out by using a descriptive analysis and panel data model. The results of the study show that the distribution of the number of working poor by province shows a variety of conditions and tends to be unequal where there are still many regions that have low unemployment rates but the number of working poor tends to be high. The study also found that the village funds program, the percentage of formal workers, and the underemployment rate had a significant effect on the number of working poor.